Perioperative ischaemic brain injury and plasma neurofilament light: a secondary analysis of two prospective cohort studies. (February 2023) - Taylor, Jennifer; Eisenmenger, Laura; Lindroth, Heidi; Booth, James; Mohanty, Rosaleena; Nair, Veena; Parker, Margaret; Kunkel, David; Rivera, Cameron; Casey, Cameron; Zetterberg, Henrik; Blennow, Kaj; et al.
Abstract: Background: Ischaemic brain infarction can occur without acute neurological symptoms (covert strokes) or with symptoms (overt strokes), both associated with poor health outcomes. We conducted a pilot study of the incidence of preoperative and postoperative (intraoperative or postoperative) covert strokes, and explored the relationship of postoperative ischaemic brain injury to blood levels of neurofilament light, a biomarker of neuronal damage. Methods: We analysed 101 preoperative (within 2 weeks of surgery) and 58 postoperative research MRIs on postoperative days 2–9 from two prospective cohorts collected at the University of Wisconsin (NCT01980511 and NCT03124303). Participants were aged >65 yr and undergoing non-intracranial, non-carotid surgery. Results: Preoperative covert stroke was identified in 2/101 participants (2%; Bayesian 95% confidence interval [CI], 0.2–5.4). This rate was statistically different from the postoperative ischaemic brain injury rate of 7/58 (12%, 4.9–21.3%; P =0.01) based on postoperative imaging. However, in a smaller group of participants with paired imaging ( n =30), we did not identify the same effect ( P =0.67). Patients with postoperative brain injury had elevated peak neurofilament light levels (median [inter-quartile range], 2.34 [2.24–2.64] log10 pg ml −1 ) compared with those without (1.86 [1.48–2.21] log10 pg ml −1 ; P =0.025). Delirium severity scores were higher in those with postoperative brain injury (19 [17–21]) compared with those without (7 [4–12]; P =0.01). Conclusion: Although limited by a small sample size, these data suggest that preoperative covert stroke occurs more commonly than previously anticipated. Plasma neurofilament light is a potential screening biomarker for postoperative ischaemic brain injury.